Genome-Wide Association Studies From Polymorphism to Personalized Medicine - Krishnarao Appasani, Ed (Cambridge University Press, 2016)
Over the last twenty years, genome-wide association studies (GWAS) have revealed a great deal about the genetic basis of a wide range of complex diseases and they will undoubtedly continue to have a broad impact as we move to an era of personalised medicine. This authoritative text, written by leaders and innovators from both academia and industry, covers the basic science as well as the clinical, biotechnological and pharmaceutical potential of these methods. With special emphasis given to highlighting pharmacogenomics and population genomics studies using next-generation technology approaches, this is the first book devoted to combining association studies with single nucleotide polymorphisms, copy number variants, haplotypes and expressed quantitative trait loci. A reliable guide for newcomers to the field as well as for experienced scientists, this is a unique resource for anyone interested in how the revolutionary power of genomics can be applied to solve problems in complex disease.